Blockchain Technology: A comprehensive review of technical characteristics, applications, and challenges - I Wayan Pio Pratama; Ondi Asroni (Jurnal Penelitian Terapan Mahasiswa, 2023)
Blockchain technology has gained significant attention in recent years due to its potential to transform a wide range of industries. This review aims to comprehensively analyze blockchain technology's technical characteristics, applications, challenges, and limitations as addressed in academic literature published between 2014 and 2021. A total of 50 articles were included in the review after being evaluated for relevance, quality, originality, clarity, and practical or theoretical implications. The results of the review indicate that research on blockchain has progressed significantly in the past decade, with a wide range of studies exploring its technical characteristics, potential applications, and challenges and limitations. Technical characteristics of blockchain include its decentralized nature, the use of cryptographic techniques, and its potential to improve efficiency and reduce the need for intermediaries. Potential applications of blockchain include finance, supply chain management, and healthcare. Challenges and limitations of blockchain include scalability, energy consumption, regulatory issues, and risks and uncertainties. The results suggest that while blockchain technology has the potential to transform industries, there is still much work to be done to address its challenges and ensure its responsible deployment.